Comparative analysis of government extension services for rice farmers the case of Magsaysay and Matanao, Davao del Sur - Legaspi, Luyjilene V. (School of Management, University of the Philippines Mindanao, 2016)
Over the past decades, there have already been various agricultural extension services implemented by the government that aimed to improve the production for rice and alleviate the live of the farmers in the Philippines. However, despite the fact that the rice sector is the center of agricultural policies and has the highest allocated budget for the National Rice Program in the country, a 100 percent rice self-sufficient Philippines is still far from happening in the next few years. Using the case of the municipalities of Magsaysay and Matanao, Davao del Sur, key informants from the LGUs and rice farmers in the community were interviewed to better understand the situation. The study revealed that the government extension services in the two municipalities have indeed a positive effect in the alleviation in the production of rice in the farming communities. On the other hand, there is a gap in the implementation of these extension services as well as to whom these extension services are being made available for. Thus, it is inevitable that the extension services provided in the two municipalities do not really meet their full potential as to addressing the needs of the rice farmers in improving their production.